2010
DOI: 10.1073/pnas.1012496107
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic spine instability and insensitivity to modulation by sensory experience in a mouse model of fragile X syndrome

Abstract: Fragile X syndrome (FXS) is the most common inherited form of mental retardation and is caused by transcriptional inactivation of the X-linked fragile X mental retardation 1 (FMR1) gene. FXS is associated with increased density and abnormal morphology of dendritic spines, the postsynaptic sites of the majority of excitatory synapses. To better understand how lack of the FMR1 gene function affects spine development and plasticity, we examined spine formation and elimination of layer 5 pyramidal neurons in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
212
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(226 citation statements)
references
References 44 publications
14
212
0
Order By: Relevance
“…BTBR mice, the inbred strain identified by behavioural screening to mimic the core behavioural deficits of ASD, also showed a similar spine phenotype. In addition to these three ASD mouse models that were analysed in this study, the Fmr1 knockout (KO) mice, a fragile X syndrome and syndromic autistic mouse model, displayed enhanced spine turnover 45,48 , further supporting the idea that an increase in synapse turnover is a common phenotype across diverse ASD mouse models.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…BTBR mice, the inbred strain identified by behavioural screening to mimic the core behavioural deficits of ASD, also showed a similar spine phenotype. In addition to these three ASD mouse models that were analysed in this study, the Fmr1 knockout (KO) mice, a fragile X syndrome and syndromic autistic mouse model, displayed enhanced spine turnover 45,48 , further supporting the idea that an increase in synapse turnover is a common phenotype across diverse ASD mouse models.…”
Section: Discussionmentioning
confidence: 80%
“…Sensory inputs of the barrel cortex can be modulated by trimming whiskers in a chess-board pattern 44 . In vivo imaging of gephyrin-GFP-( þ ) and ( À ) spines in the barrel cortex over 2 days at postnatal week 3, combined with chess-board whisker trimming, revealed increase in gain of spines receiving inputs from intracortical neurons in wild-type mice 44,45 ( Fig. 7a,b).…”
Section: Nature Communications | Doi: 101038/ncomms5742mentioning
confidence: 99%
“…Studies in Fmr1 KO mice have further revealed that FMRP regulates protein synthesis-dependent axon pruning, dendritic spine elimination, and actin-dependent stabilization of spines. In Fmr1 KO mice, disruption of this regulation leads to abnormal rates of dendritic spine turnover, delayed stabilization of dendritic spines during development, and absence of experience-induced dendritic spine modulation Li et al, 2009;Chen et al, 2010;Cruz-Martin et al, 2010;Pan et al, 2010;Pfeiffer et al, 2010;Scotto-Lomassese et al, 2011).…”
Section: Abnormal Dendritic Spine Morphology In Fxsmentioning
confidence: 99%
“…Only recently, studies have begun to analyze the function of FMRP for dendritic spine morphology in vivo in living mice (Cruz-Martin et al, 2010;Pan et al, 2010). These analyses revealed that dendritic spines are more transient and show delayed stabilization in Fmr1 KO mice (reviewed in Portera-Cailliau, 2011).…”
Section: Abnormal Dendritic Spine Morphology In Fxsmentioning
confidence: 99%
“…Without affecting spine formation, deleting β-adducin, which regulates actin, perturbed the process by which nascent spines establish functional synapses and impaired long-term memory (19). Fragile X syndrome, a common form of mental retardation, exhibits a higher than normal density of spines but more of them exhibit an immature morphology and their turnover is not affected by sensory experience (9,20). Conversely, the protein Telencephalin arrests the maturation of spines and its removal enhances several forms of learning (13,21,22).…”
mentioning
confidence: 99%